Provision of small‐quantity lipid‐based nutrient supplements does not improve intestinal health among rural Malawian children. Issue 3 (7th February 2022) - Liu, Zhifei; Ashorn, Ulla; Chingwanda, Chilungamo; Maleta, Kenneth; Hallamaa, Lotta; Matchado, Andrew; Kortekangas, Emma; Dewey, Kathryn G; Ashorn, Per; Fan, Yue‐Mei
Abstract: Lipid‐based nutrient supplements (LNS) have been found to improve child growth and reduce child mortality. However, the mechanistic pathways for these improvements warrant exploration. One potential pathway is linked to improvement in intestinal health. Our study aimed to test a hypothesis that small‐quantity LNS (SQ‐LNS) could reduce the levels of intestinal inflammation, repair and permeability of children. As intestinal health markers we measured fecal calprotectin, regenerating 1B protein (REG1B) and alpha‐1‐antitrypsin concentrations at 18 months of age (after 12 months of supplementation) and 1 year later (12 months after cessation of supplementation). In this analysis, we included data of 735 children who participated in a randomised dietary supplementation trial in rural Malawi; 243 children who received 20 g/day SQ‐LNS from 6 to 18 months of age were in the SQ‐LNS group, while the others who received no dietary supplementation during this period were in the control group. At 18 months of age, the mean concentrations of calprotectin, REG1B and alpha‐1‐antitrypsin were 241, 105 µg/g and 7.1 mg/dl, respectively, in the SQ‐LNS group, and 224, 105 µg/g and 7.4 mg/dl, respectively, in the control group, and did not differ between the SQ‐LNS and control groups. We conclude that SQ‐LNS provision did not have an impact on children's intestinal health in rural Malawi. Abstract : Lipid‐based nutrient supplements (LNS) have been found to improve child growth and reduce child mortality. One potential pathway is linked to improvement in intestinal health. Our study in rural Malawi did not observe an effect of small‐quantity LNS on children's intestinal health. Key messages: Provision of small‐quantity lipid‐based nutrient supplements (SQ‐LNS) has proven useful in the promotion of children's growth but the mechanistic pathways are unclear. In a sample of rural Malawian children, provision of 20 g/day SQ‐LNS to 6‐ to 18‐month‐old children had no impact on concentrations of faecal calprotectin, REG1B, or alpha‐1‐antitrypsin at 18 months (which represented intestinal inflammation, repair and permeability). A 12‐month provision of SQ‐LNS, by itself, may not be sufficient to improve children's intestinal health in conditions like those of rural Malawi.